Web application based on the Fuzzy Analytic Hierarchy Process (FAHP) to optimize the selection of suppliers - Rantes, Ronnie (2024)
Small and medium-sized enterprises have always proven to be crucial to national economies, yet many of them fail for a variety of reasons. One of them is selecting an inadequate supplier that does not meet the needs that the company requires to properly perform its core business. Therefore, this project proposes to develop a web application to select the best supplier option for a company. The main objective is to assist in decision making and reduce costs with a web application that implements the Fuzzy Analytic Hierarchy Process (FAHP), based on a series of criteria and priorities chosen by the company itself. After testing the application, the result was a relative score assigned to each alternative, thus identifying the supplier with the highest value as the most optimal choice. Finally, through the measurement of the consistency ratio for each pair matrix developed, it was possible to verify that the solution achieved acceptable results that do not exceed the range of inconsistency.